Flow cytometry-based evaluation of the bacterial removal efficiency of a blackwater reuse treatment plant and the microbiological changes in the associated non-potable distribution network - Whitton, Rachel; Fane, Sarah Elizabeth; Jarvis, Peter; Tupper, Martyn; Raffin, Marie; Coulon, Frederic; Nocker, Andreas (Elsevier, 2018)
The study evaluated the changes in bacterial numbers across a full-scale membrane bioreactor (MBR) blackwater reuse system. Flow cytometry was used to quantify total and intact bacterial concentrations across the treatment train and during distribution of the recycled water. Membrane passage reduced bacterial numbers by up to 5-log units resulting in coliform-free permeate. A 2-log increase in bacterial cell concentration was subsequently observed after the granular activated carbon unit followed by a reduction in intact cells after chlorination, which corresponds to an overall intact bacteria removal of 3.4-log units. In the distribution network, the proportion of intact cells greatly depended on the free chlorine residual, with decreasing residual enabling regrowth. An initial target of 0.5 mg L−1 free chlorine ensured sufficient suppression of intact cells for up to 14 days (setting the time intervals for system flushes at times of low water usage). Bacterial regrowth was only observed when the free chlorine concentration was below 0.34 mg L−1. Such loss of residual chlorine mainly applied to distant points in the distribution network from the blackwater reuse treatment plant (BRTP). Flushing these network points for 5 min did not substantially reduce cell numbers. At points closer to the BRTP, on the other hand, flushing reduced cell numbers by up to 1.5-log units concomitant with a decreasing proportion of intact cells. Intact cell concentrations did not correlate with DOC, total nitrogen, or soluble reactive phosphate, but it was shown that dead biomass could be efficiently converted into new biomass within seven days.
Keywords: Blackwater reuse; Water recycling; MBR; Distribution system; Chlorination; Flow cytometry